Natural law foundations to analyze STC N° 09332-2006-PA/TC regarding new family structures - Bayona Salcedo, Ana Guadalupe (2018)
The purpose of this communication some foundation natural law in order to analyze the STC No. O9332-2006-PA / TC regarding new family structures recognized by the Constitutional Court. This regard should be noted that certainly Peruvian society experienced in recent years a significant change in the family institution is concerned, as a result of the adaptation process to the present time, why have been a number of similar structures to the family "with a different dynamic," (basis 9) living with the family in the social fabric. The advent of these family structures has required the state a degree of protection. Through the aforementioned judgment, the Constitutional Court has recognized "families that were generated with different structures than the traditional, such as those arising from de facto unions, single (...) and stepfamilies" (basis 7) or assembled; thus broadening the constitutional concept of family as referred to in Article 4 "is a natural and fundamental institution of society" allowing for a concept of pluralized family institution, away from the model guaranteed in the Constitution. We believe that this assimilation will generate a weakening of the family institution.